1995
DOI: 10.1038/bjc.1995.336
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for optimising photodynamic therapy: second-generation photosensitisers in combination with mitomycin C

Abstract: Summary Mechanisms for improving photodynamic therapy (PDT) were investigated in the murine RIFI tumour using meso-tetrahydroxyphenylchlorin (m-THPC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…The results from this study demonstrated that Foscan PDT was relatively ineffective at controlling the regrowth of H-MESO1 xenografts when illumination was given at intervals of 424 h. This is in agreement with several other studies in rodent tumours and human xenografts grown in nude mice (Ris et al, 1993;Morlet et al, 1995;Van Geel et al, 1995;Veenhuizen et al, 1997a) , but it differs from clinical experience. Standard clinical protocols for Foscan PDT involve illumination with 20 -30 J cm À2 at 4 days after a drug dose of 0.15 mg kg À1 .…”
Section: Discussionsupporting
confidence: 91%
“…The results from this study demonstrated that Foscan PDT was relatively ineffective at controlling the regrowth of H-MESO1 xenografts when illumination was given at intervals of 424 h. This is in agreement with several other studies in rodent tumours and human xenografts grown in nude mice (Ris et al, 1993;Morlet et al, 1995;Van Geel et al, 1995;Veenhuizen et al, 1997a) , but it differs from clinical experience. Standard clinical protocols for Foscan PDT involve illumination with 20 -30 J cm À2 at 4 days after a drug dose of 0.15 mg kg À1 .…”
Section: Discussionsupporting
confidence: 91%
“…The partial and reversible reduction in tumor perfusion induced by 6 hr-interval PDT, due to the low drug level found in the tumor vasculature at this time, may account for the limited effect on the tumor eradication observed with this PDT regimen. Similar to the observations made with other vasculature-targeting photosensitizers, 19,22,23 our results indicate that, after tumor vasculature damage induced by PDT with hypericin, tumor cells are killed mainly by the resultant oxygen and nutrient deprivation, which leads to the delayed tumor cell death. Indeed, this PDT induced vascular damage can also be found histologically.…”
Section: Type Of Cell Death After Hypericin-mediated Pdtsupporting
confidence: 89%
“…19 Briefly, at various times after PDT, tumors were removed from surrounding normal tissues, weighed and minced under sterile and subdued light conditions. The minced tumor was disaggregated in 5 ml sterile PBS containing 0.05% protease (Sigma Type IX), 0.02% DNase (Sigma Type I) and 0.02% collagenase (Sigma Type IV) under continuous stirring at 37°C for 40 min.…”
Section: In Vivo/in Vitro Cell Survival Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Various laboratory investigators have therefore explored the approach of combining bioreductive drugs with photodynamic therapy in order to exploit the PDT-induced hypoxia and enhance the tumoricidal effect of the bioreductive drug (Evensen and Moan, 1988;Gonzalez et al, 1986;Winther et al, 1988;Bremner et al, 1992;Baas et al, 1994;Van Geel et al, 1995). In most cases an advantage was observed for the combination therapy although exact timing of the administration of the bioreductive drug appeared to be important (Evensen and Moan, 1988;Winther et al, 1988).…”
Section: Discussionmentioning
confidence: 99%